Pathway-Based Drug Response Prediction Using Similarity Identification in Gene Expression - Madani Tonekaboni, Seyed Ali; Beri, Gangesh; Haibe-Kains, Benjamin (Frontiers in Genetics, 2020)
Lapatinib and Trastuzumab (Herceptin) are targeted therapies designed for patients with HER2+ breast tumors. Although these therapies improved survival rates of patients with this tumor type, not all the patients harboring HER2 amplification respond to these drugs. The NeoALTTO clinical trial was designed to test whether a higher response rate can be achieved by combining Lapatinib and Trastuzumab. Although combination therapy showed almost double the response rate compared to the monotherapies, 40% of the patients did not respond to the treatment. In this study, we sought to identify biomarkers of HER2+ breast cancer patients’ response to drugs relying on gene expression profiles of tumors. We show that univariate gene expression-based biomarkers are significant but weak predictors of drug response. We further show that pathway activities, estimated from gene expression patterns quantified using the recent transcriptional similarity coefficient (TSC) between the tumor samples, yield high predictive value for therapy response (concordance index >0.8, p<0.05). Moreover, machine learning models, built using multiple algorithms including: logistic regression, naive Bayes, random forest, k-nearest neighbour and support vector machine, for predicting drug response in NeoALTTO clinical trial resulted in lower performance compared to our pathway based approach. Our results indicate that transcriptional similarity of biological pathways can be used to predict Lapatinib and Trastuzumab response in HER2+ breast cancer.